PENDAMPINGAN PENGELOLAAN KEUANGAN DAN MANAJEMEN AMAL USAHA MUHAMMADIYAH BIDANG PENDIDIKAN KABUPATEN JEMBER BERBASIS NILAI-NILAI KEISLAMAN - Aspirandi, Rendy Mirwan; Thamrin, Mohammad; Satoto, Eko Budi; Halim, Moh.; Dewi, Nindi Kumala; Anggraeni, Novi (Abdi Panca Marga, 2024)
Financial management in an entity is very important, both business and non-business entities. Well-managed finances are the key to healthy entity management (Rodiah et al., 2020). The phenomenon of decreasing the number of AUMDik students in Jember Regency occurred in several schools. This phenomenon must not be allowed to drag on. The problem of decreasing the number of students in several AUMDiks occurs partly because of unhealthy financial management in the AUMDiks concerned (Pituringsih et al., 2020). To overcome and anticipate the continued decline in the number of students in several AUMDik in Jember Regency (Dewi & Renggana, 2022), the Community Service Team has prepared a cutting-edge breakthrough, namely a follow-up activity in the form of assistance in preparing financial reports and managing management through a system provided by PP Muhammadiyah can help AUMDik monitor the financial condition of the AUMDik concerned. This community service method is carried out. Activities are carried out online and offline (blended learning). Online implementation using the Zoom Meeting Application. The community service team will carry out initial observations at SD Muhammadiyah 1 Jember, SMA Muhammadiyah 3 Jember, SD Muhammadiyah 7 Semboro, SD Muhammadiyah 1 Balung and MI Muhammadiyah 3 Wonoasri. The process of implementing the service begins with the presentation of general material regarding AUM financial management, material on the input process in the SIAS financial system from MMT and finally assistance with the financial management process. The presentation of AUM's financial management material generally discusses AUM's goals in carrying out healthy financial management, tips for success in managing AUM's finances and techniques for increasing the number of students. The material on the process of inputting financial data in the SIAS system discusses the steps on how to create school profile data, the required account name data, grouping accounts according to the type of account in the system, how to fill in the balances for each account, determining the type of asset and preparing reports finance. The mentoring process starts with assistance in filling out the school profile and filling in each account in SIAS. References Ariesta, C., & Nurhidayah, F. (2020). Penerapan Penyusunan Laporan Keuangan Neraca Berbasis SAK-ETAP Pada UMKM. Jurnal Akuntansi, 9(2), 194–203. https://doi.org/10.37932/ja.v9i2.142 Cahyono, D. (2020). Kapasitas Sumber Daya Manusia, Pemanfaatan Teknologi Informasi Dan Pengendalian Intern Terhadap Nilai Informasi Pelaporan Keuangan. International Journal OF Social Science AND Business, 4(1), 116–122. Dahrani, D., Saragih, F., & Ritonga, P. (2022). Model Pengelolaan Keuangan Berbasis Literasi Keuangan dan Inklusi Keuangan : Studi pada UMKM di Kota Binjai. Owner, 6(2), 1509–1518. https://doi.org/10.33395/owner.v6i2.778 Dewi, L., & Renggana, R. M. (2022). Pendampingan Pengelolaan Keuangan Masjid Untuk Peningkatan Akuntabilitas Sosial. Jurnal Ilmiah Pangabdhi, 8(2), 96–100. https://doi.org/10.21107/pangabdhi.v8i2.16730 Kompas.com. (2022). Siswa SD Muhammadiyah 4 Surabaya “Study Tour” ke Jepang, Berapa Biayanya? Halaman all - Kompas.com. Https://Www.Kompas.Com/Tren/Read/2023/06/13/133000565/Siswa-Sd-Muhammadiyah-4-Surabaya-Study-Tour-Ke-Jepang-Berapa-Biayanya-?Page=all. https://www.kompas.com/tren/read/2023/06/13/133000565/siswa-sd-muhammadiyah-4-surabaya-study-tour-ke-jepang-berapa-biayanya-?page=all Lazismu Jatim. (2023). AUM se-Jatim. Https://Info.Lazismujatim.Org/Aum-Se-Jatim/. https://info.lazismujatim.org/aum-se-jatim/ Niati, A., Suhardjo, Y., Wijayanti, R., & Hanifah, R. U. (2019). Pelatihan Pengelolaan Manajemen Keuangan dan Pelaporan Keuangan Akuntansi Pesantren bagi Pengelola Yayasan Pondok Pesantren X di Kota Semarang. Jurnal Surya Masyarakat, 2(1), 76. https://doi.org/10.26714/jsm.2.1.2019.76-79 Pituringsih, E., Herwanti, R. T., & Handajani, L. (2020). Penyuluhan dan Pedampingan Penyusunan Pengelolaan Keuangan Panti Asuhan “Darus - Shiddiqien NW” Mertak Paok, Desa Mekar Bersatu Kecamatan Batukliang Kabupaten Lombok Tengah. Jurnal Gema Ngabdi, 2(3), 285–292. https://doi.org/10.29303/jgn.v2i3.116 Ariesta, C., & Nurhidayah, F. (2020). Penerapan Penyusunan Laporan Keuangan Neraca Berbasis SAK-ETAP Pada UMKM. Jurnal Akuntansi, 9(2), 194–203. https://doi.org/10.37932/ja.v9i2.142 Cahyono, D. (2020). Kapasitas Sumber Daya Manusia, Pemanfaatan Teknologi Informasi Dan Pengendalian Intern Terhadap Nilai Informasi Pelaporan Keuangan. International Journal OF Social Science AND Business, 4(1), 116–122. Dahrani, D., Saragih, F., & Ritonga, P. (2022). Model Pengelolaan Keuangan Berbasis Literasi Keuangan dan Inklusi Keuangan : Studi pada UMKM di Kota Binjai. Owner, 6(2), 1509–1518. https://doi.org/10.33395/owner.v6i2.778 Dewi, L., & Renggana, R. M. (2022). Pendampingan Pengelolaan Keuangan Masjid Untuk Peningkatan Akuntabilitas Sosial. Jurnal Ilmiah Pangabdhi, 8(2), 96–100. https://doi.org/10.21107/pangabdhi.v8i2.16730 Kompas.com. (2022). Siswa SD Muhammadiyah 4 Surabaya “Study Tour” ke Jepang, Berapa Biayanya? Halaman all - Kompas.com. Https://Www.Kompas.Com/Tren/Read/2023/06/13/133000565/Siswa-Sd-Muhammadiyah-4-Surabaya-Study-Tour-Ke-Jepang-Berapa-Biayanya-?Page=all. https://www.kompas.com/tren/read/2023/06/13/133000565/siswa-sd-muhammadiyah-4-surabaya-study-tour-ke-jepang-berapa-biayanya-?page=all Lazismu Jatim. (2023). AUM se-Jatim. Https://Info.Lazismujatim.Org/Aum-Se-Jatim/. https://info.lazismujatim.org/aum-se-jatim/ Niati, A., Suhardjo, Y., Wijayanti, R., & Hanifah, R. U. (2019). Pelatihan Pengelolaan Manajemen Keuangan dan Pelaporan Keuangan Akuntansi Pesantren bagi Pengelola Yayasan Pondok Pesantren X di Kota Semarang. Jurnal Surya Masyarakat, 2(1), 76. https://doi.org/10.26714/jsm.2.1.2019.76-79 Pituringsih, E., Herwanti, R. T., & Handajani, L. (2020). Penyuluhan dan Pedampingan Penyusunan Pengelolaan Keuangan Panti Asuhan “Darus - Shiddiqien NW” Mertak Paok, Desa Mekar Bersatu Kecamatan Batukliang Kabupaten Lombok Tengah. Jurnal Gema Ngabdi, 2(3), 285–292. https://doi.org/10.29303/jgn.v2i3.116 Qomariah, N. (2012). Pengaruh kualitas layanan dan citra institusi terhadap kepuasan dan loyalitas pelanggan (studi pada universitas muhammadiyah di Jawa Timur). In Jurnal Aplikasi Manajemen (Vol. 10, Issue 1, pp. 177–187). Rodiah, S., Satria, W., Putri, A. A., Azmi, Z., Suci, R. G., & Marlina, E. (2020). Akuntabilitas Pengelolaan Keuangan Pada Pondok Pesantren Bahrul Ulum Pantai Raja Kampar. COMSEP: Jurnal Pengabdian Kepada Masyarakat, 1(1), 134–138. Tatik Amani. (2018). Penerapan SAK-EMKM Sebagai Dasar Penyusunan Laporan Keuangan UMKM (Studi Kasus di UD Dua Putri Solehah Probolinggo). ASSETS: Jurnal Ilmiah Akuntansi, Keuangan Dan Pajak, 2(2), 12–20.